Labour market policy if the general public was in charge - Stijn Baert; Els Clays; Eva Derous; Bert George; Brecht Neyt; Eveline Schollaert; Bart Wille (Institute of Labor Economics (IZA), 2021)
This study uses survey data among both a random sample (N = 500) and a convenience sample (N = 2,919) of Flemish adults to assess public support for 24 potential labour market reforms. The results show that there is a lot of public support for (both encouraged and mandatory) training and community service for the unemployed and for the so-called 'job bonus', which are all reforms planned by the Flemish government Jambon I. However, there is little public support for reforms which should make the - apparently strongly desired - increase of the minimum pension to 1,500 euro after taxes possible, such as gradually eliminating early retirement possibilities, decreasing how much equated periods (such as periods of sick leave and unemployment) count towards pension accrual, and (partly) unlinking wages from seniority. This indicates that the end-of-career-debate that the Belgian federal government De Croo I wants to have will not be an easy one. For the planned increased monitoring to fight social and fiscal fraud, there is, however, a lot of public support. Somewhat surprisingly, there is little public support for reforms which aim to strengthen the position of women on the labour market, such as more quota for women in boards of directors in private companies, more parental leave for couples who divide this leave more equally, and increased paternity leave from 10 to 20 days.
Keywords: J0; J28; J38; J58; J68; J78; 330; labour market policy; labour market reforms; public support